(untitled) (Materiali di Estetica. Terza serie, 2022)
The article is a direct witness of the birth of Fondazione Corrente given by one of his President. It underlines the relations between the historical movement of “Corrente” in 1938 and the new venture in 1978, focusing on the political engagement